POLA KOMUNIKASI ORANG TUA DALAM MENANGANI KEMAMPUAN BERBICARA PADA ANAK PENDERITA SPEECH DELAY - Adhi Wiranata, I Putu Reza; S.S., M.A., Tsuroyya, (The Commercium, 2024)
This research discusses family communication, giving gadgets to children with speech delay, and providing stimulation to children at home. This study involved informants who were parents of children with speech delays. The results of the research show that democratic communication patterns are effectively applied to children with speech delays, giving children the freedom to express opinions. Giving gadgets needs to be supervised and given a time limit, with a focus on applications that support children’s development. Stimulation at home involves monitoring gadget use, light communication, object recognition, oral stimulation, and attention to the child’s eating patterns. Apart from that, stimulation at the child development center is advanced with the aim of improving children’s growth and development. Parents have an important role in consistently providing stimulation to accelerate the growth of children with speech delays. By applying appropriate stimulation, it is hoped that children can overcome speech delays and achieve optimal growth and development. Keywords: Parents, children, speech delay, democratis communication patterns, and stimulation.